Peran Metadata Management dalam Meningkatkan Kualitas Data Efesiensi Pengambilan Keputusan - Aprilia Eka Putri; Muhammad Irwan Padli Nasution (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the era of digital transformation, organizations face the huge challenge of managing data that is constantly increasing in volume, variety, and speed. Metadata, as